The Influence of Sandpaper Letter Media on Pre-Reading Skills in Children Aged 5-6 - Epi Supriyani Siregar; Ika Purnama Sari; Estri Oktarena Ikrarini; Elce Purwandari; Ari Setiawan; Ambrosius Fernus Ndruru (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Pre-reading skills are a crucial foundation for early childhood literacy development; however, conventional teaching methods often lack multisensory engagement, which limits their effectiveness. While previous studies have acknowledged the importance of sensory experiences, a gap remains in empirical evidence that quantitatively demonstrates the impact of specific tactile media, such as Sandpaper Letters, on pre-reading abilities in children aged 5-6 within localized educational contexts. This study aims to analyze the effect of Sandpaper Letter media on the pre-reading skills of children in this age group. Using a quasi-experimental method with a pretest-posttest control group design, the research involved 30 children from a kindergarten. The experimental group received learning interventions using Sandpaper Letters, while the control group used conventional methods. Data were collected through pre-reading skill tests and analyzed using normality tests (Kolmogorov-Smirnov) and an independent t-test. The results showed a significant improvement in the experimental group's letter recognition, phonemic awareness, and simple word formation skills, with a t-count of 1.934 exceeding the t-table of 1.729. The study concludes that Sandpaper Letter media is a practical, multisensory-based tool for significantly enhancing the pre-reading skills of children aged 5-6 years, offering a valuable strategy for early childhood educators. Keterampilan pra-membaca merupakan fondasi krusial bagi perkembangan literasi anak usia dini, namun metode pengajaran konvensional seringkali kurang melibatkan multisensori, sehingga membatasi efektivitasnya. Meskipun studi-studi terdahulu telah mengakui pentingnya pengalaman sensorik, masih terdapat kesenjangan bukti empiris yang secara kuantitatif mendemonstrasikan dampak media taktil spesifik, seperti Sandpaper Letter, terhadap kemampuan pra-membaca anak usia 5-6 tahun dalam konteks pendidikan lokal. Penelitian ini bertujuan untuk menganalisis pengaruh media Sandpaper Letter terhadap keterampilan pra-membaca anak pada kelompok usia tersebut. Dengan menggunakan metode kuasi-eksperimen dengan desain pretest-posttest control group, penelitian melibatkan 30 anak dari satu taman kanak-kanak. Kelompok eksperimen menerima intervensi pembelajaran menggunakan Sandpaper Letter, sementara kelompok kontrol menggunakan metode konvensional. Data dikumpulkan melalui tes keterampilan pra-membaca dan dianalisis menggunakan uji normalitas (Kolmogorov-Smirnov) dan uji-t independen. Hasil penelitian menunjukkan peningkatan yang signifikan pada kelompok eksperimen dalam hal pengenalan huruf, kesadaran fonemik, dan kemampuan menyusun kata sederhana, dengan nilai t-hitung 1,934 yang melebihi t-tabel 1,729. Studi ini menyimpulkan bahwa media Sandpaper Letter merupakan alat berbasis multisensori yang efektif untuk meningkatkan keterampilan pra-membaca anak usia 5-6 tahun secara signifikan, sehingga menawarkan strategi yang berharga bagi pendidik anak usia dini.